Finite element solution of MHD mixed convection in a channel with a fully or partially heated cavity - Rahman, M. M.; Öztop, Hakan Fehmi; Saidur, R.; Mekhilef, S.; Al-Salem, Khaled (Pergamon-Elsevier Science Ltd, 2013)
In the present study, combined convection in an open channel with a square cavity which has a partially or fully heated on left side to simulate assisting flow is carried out numerically using finite element method. A computer code is developed to solve governing equations. Fluid flows through a channel which has a square open cavity. The left side of the cavity is heated fully or partially with an isothermal heater. Inlet temperature of the fluid is colder than that of heater. Remaining parts are adiabatic. Thus, two cases are tested as fully heated side (Case I) and partially heated side (Case 2). Effects of magnetic field are tested on flow and temperature field inside the channel. The studied parameters are Rayleigh numbers (Ra) and Hartmann number (Ha). It was observed that length of heater becomes insignificant on flow field for higher values of Hartmann number. On the contrary, higher heat transfer is formed for partial heater at the higher values of Rayleigh number. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Channel; Open cavity; Magnetic field; Partial heater; Numerical solution